PENGGUNAAN MEDIA KARTU POSITIF-NEGATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Handoyo, Adityas Budi; Nisa, Ana Fitrotun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by low learning outcomes and lack of learning motivation when learning integer arithmetic operations. Therefore, this research aims to improve student learning outcomes through the use of positive and negative card learning media. This research is classroom action research whose subjects are class VI students at one of the Kebumen Regency State Elementary Schools for the 2022/2023 school year. This classroom action research was carried out in two cycles, where in each condition four stages of activity were carried out starting with action planning, action implementation, observation and ending with reflection. The results of this Classroom Action Research show that in the Pre-Cycle conditions, students' learning completeness only reached 20.8%, then in Cycle 1, students' learning completeness increased to 62.5%, and in Cycle 2, students' learning completeness increased again to 87.5%. This classroom action research can be concluded that using positive-negative card media has been proven to improve student learning outcomes.